Temporal trends in atrial fibrillation recurrence rates after ablation between 2005 and 2014: a nationwide Danish cohort study. (28th August 2017) - Pallisgaard, Jannik Langtved; Gislason, Gunnar Hilmar; Hansen, Jim; Johannessen, Arne; Torp-Pedersen, Christian; Rasmussen, Peter Vibe; Hansen, Morten Lock
Abstract: Aims: During the last decade, ablation has increasingly been used in rhythm control management of patients with atrial fibrillation (AF). Over time, experience and techniques have improved and indications for ablation have expanded. The purpose of this study was to investigate whether the recurrence rate of AF following ablation has improved during last decade. Methods and results: Through Danish nationwide registers, all patients with first-time AF ablation, between 2005 and 2014 in Denmark were identified. Recurrent AF after ablation was identified with 1 year follow-up. A total of 5425 patients undergoing first-time ablation were included. While patient median age increased over time the median AF duration prior to ablation decreased. The rates of recurrent AF decreased from 45% in 2005–2006 to 31% 2013–2014 with the relative risk of recurrent AF almost halved with an odds ratio of 0.57 [95% confidence intervals (95% CI) 0.47–0.68] in 2013–2014 compared with patients undergoing ablation in 2005–2006. Female gender, hypertension, AF duration >2 years, and cardioversion within 1 year prior to ablation were all associated with an increased risk of recurrent AF. Conclusion: One year risk of recurrent AF following first-time ablation has almost halved from 2006 to 2014. Hypertension, female sex, cardioversion 1 year prior to ablation, and AF duration for more than 2 years all increased the associated risk of recurrent AF.